Eye lens radiocarbon reveals centuries of longevity in the Greenland shark ( Somniosus microcephalus ) - Nielsen, Julius; Hedeholm, Rasmus B.; Heinemeier, Jan; Bushnell, Peter G.; Christiansen, Jørgen S.; Olsen, Jesper; Ramsey, Christopher Bronk; Brill, Richard W.; Simon, Malene; Steffensen, Kirstine F.; Steffensen, John F. (Science, 2016)
Deep living for centuries We tend to think of vertebrates as living about as long as we do, give or take 50 to 100 years. Marine species are likely to be very long-lived, but determining their age is particularly difficult. Nielsen et al. used the pulse of carbon-14 produced by nuclear tests in the 1950s—specifically, its incorporation into the eye during development—to determine the age of Greenland sharks. This species is large yet slow-growing. The oldest of the animals that they sampled had lived for nearly 400 years, and they conclude that the species reaches maturity at about 150 years of age. Science , this issue p. 702